Evaluation of the Larvicidal Potential of the Essential Oil Pogostemon cablin (Blanco) Benth in the Control of Aedes aegypti - Lizandra Lima Santos; Lethicia Barreto Brandão; Rosany Lopes Martins; Erica de Menezes Rabelo; Alex Bruno Lobato Rodrigues; Camila Mendes da Conceição Vieira Araújo; Talita Fernandes Sobral; Allan Kardec Ribeiro Galardo; Sheylla Susan Moreira da Silva de Ameida (MDPI AG, 2019)
The objective of this work was to collect information on the chemical constituents that demonstrate the larvicidal activity against Aedes aegypti, as well as the antioxidant, microbiological, and cytotoxicity potential of the essential oil of Pogostemon cablin leaves. The chemical characterization was performed by gas chromatography coupled to mass spectrometer (GC-MS). The larvicidal activity was performed according to the protocol of the World Health Organization. The antioxidant activity was evaluated through the sequestering capacity of 2,2-diphenyl-1-picryl-hydrazine (DPPH). As for the microbiological evaluation, the microdilution technique was used, according to the protocol of the Clinical and Laboratory Standards Institute. The cytotoxic activity was evaluated against the larvae of Artemia salina. The species P. cablin presented the following compounds: Patchouli alcohol (33.25%), Seyshellene (6.12%), α-bulnesene (4.11%), Pogostol (6.33%), and Norpatchoulenol (5.72%), which was in synergy with the other substances may significantly potentiate the larvicidal action of the species with the LC50 of 28.43 μg·mL−1. There was no antioxidant activity, however, it presented antimicrobial activity against all bacteria tested with Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) of 62.5 μg·mL−1. The species demonstrated significant toxic action with LC50 of 24.25 μg·mL−1. Therefore, the P. cablin species showed significant larvicidal potential, antimicrobial activity, the absence of antioxidant action, and high toxicity.